Menkes disease in affected females: The clinical disease spectrum. (26th November 2014) - Smpokou, Patroula; Samanta, Monisha; Berry, Gerard T.; Hecht, Leah; Engle, Elizabeth C.; Lichter‐Konecki, Uta
<x xml:space="preserve">Abstract</x> Menkes disease (MD; OMIM 309400) is an X‐linked, neurodegenerative disorder resulting from deficient activity of copper‐dependent enzymes and caused by alterations in the APT7A gene. In its classic form, it manifests in boys with hypotonia, seizures, skin and joint laxity, hair twisting (pili torti), cerebrovascular tortuosity, and bladder diverticulae. Menkes disease phenotypes have been reported in females with X; autosome translocations‐ disrupting ATP7A gene function‐ or ATP7A gene alterations. Those females manifest variable clinical findings, some of which, such as pili torti, seizure presence and/or age of onset, cerebrovascular tortuosity, degree of intellectual disability, and bladder divericulae are largely under‐reported and under‐studied. Here, we report on three females with Menkes disease and variant phenotypes, sharing characteristic features, one with classic Menkes disease and two with Menkes disease variants. We conclude that Menkes disease in females manifests with a variable spectrum of clinical findings but a few are uniformly present such as neurodevelopmental disability, hypotonia, and connective tissue findings. Others, such as seizures, cerebral atrophy, and cerebrovascular tortuosity may be present but are under‐reported and under‐ studied. We propose that the diagnosis of Menkes disease or variants in females with suspicious clinical findings is an important one to consider as early treatment with parenteral copper may be considered. The effect of this treatment on the disease course in females with MD is unknown and remains to be seen. © 2014 Wiley Periodicals, Inc.